Comparing dominant hand grip strength between housewives and female bank clerks in Ujjain city: an observational study - Mishra, Ruchi; Bijlwan, Aanchal; Bajpai, Sanket; Jaiswal, Ashish; Sethiya, Deepa; Gidwani, Laxman; Gidwani, Mayuri; Jain, Sakshi; Bhawar, Nandita (International Journal of Research in Medical Sciences, 2024)
Background: The human hand, comprising complex musculoskeletal structures including major joints and numerous muscles, plays a crucial role in daily activities. Handgrip strength (HGS) is a key indicator of muscle strength and overall physical fitness. Factors such as posture, age, and physical activity influence HGS. This study aims to compare HGS between housewives and female bank clerks in Ujjain City, given their distinct daily physical activities. Method: This observational study was conducted over two months in Ujjain, involving 30 women aged 25-35 years, divided into two groups: housewives (n=15) and bank clerks (n=15). Participants were selected through purposive sampling and provided written informed consent. Exclusion criteria included musculoskeletal or neurological deficits, pregnancy, unwillingness to participate, and metabolic disorders. Results: The mean age of housewives was 28.60 years, and for bank clerks, it was 27.60 years. Housewives demonstrated significantly higher HGS across all three readings compared to bank clerks. The first reading showed housewives with a mean strength score of 15.80 kg and bank clerks with 10.40 kg (p=0.004). The second reading showed mean scores of 11.60 kg for housewives and 7.27 kg for bank clerks (p<0.001). The third reading recorded 8.93 kg for housewives and 5.53 kg for bank clerks (p=0.004). Conclusion: The study reveals that housewives exhibit higher HGS compared to female bank clerks, likely due to the more physically demanding nature of household tasks. These findings align with previous research indicating that physical activity, including domestic chores, positively impacts muscle strength.